Crisis and class inequality in Argentina: a new analysis using household survey data - Féliz, Mariano; Millón, María Emilia (2022)
This paper explains how the stagnation and crisis in Argentina (2009?2020) reshaped the standard of living of the working class and how their effects are reflected through inequality indexes. Many studies have used quintile stratification for inequality analysis. Following the traditions of Marxian/structural theoretical frameworks, we analyse inequality by defining the different factions within the working class, estimating the Socio Occupational Condition (CSO) from Census Data. This strategy allows us building different strata within the working classes from information on regular surveys. We work with the data from the Permanent Survey of Households (EPH) of Argentina. We use bootstrapping techniques to strengthen our estimations of mean income, too, in order to improve our analysis of the difference between classes and variance's income estimator. We analyse the evolution of inequality with several generalized entropy indexes. These indexes allow us to describe the composition of inequality between the different classes and within each class. We complement the analysis with macroeconomic estimates of income distribution to include estimates for income appropriation from other social classes. We study how macroeconomic developments and policies during the recent crisis have affected inequality.
Keywords: Inequality; Class structure; Argentina; Crisis; EPH